Elaboration of an index of regional development strategies for indigenous communities - García-Vázquez, Rafael; López-Santiago, Marco Andrés; Morales-Becerril, Carlos de Jesús; Sánchez-Toledano, Blanca Isabel; Medina-Cuéllar, Sergio Ernesto; López-Santiago, Andrés Aurelio (Frontiers in Sustainable Food Systems, 2025)
IntroductionThis study addressed the need to design development strategies that leverage the endogenous resources of indigenous communities. The municipality of Filomeno Mata, Veracruz, Mexico, was selected as a case of study to validate the proposed methodology. The main objective was to develop an effective approach to regional development through the construction of two key indices: the Strategy Suitability Index for Regional Development (IIDR-GM) and the Strategy Adoption Index (IADR).MethodsA mixed-methods and multidisciplinary framework was employed, combining statistical analyses with qualitative tools. The methods included the Kruskal–Wallis test, goodness-of-fit tests, and the sign test for two paired simples with normal approximation. In parallel, a Participatory Rural Appraisal (PRA) was conducted.ResultsThe IIDR-GM and IADR proved to be effective tools for evaluating development strategies. These indices captured the level of acceptance of sustainable interventions tailored to local needs, based on endogenous natural resources and ancestral knowledge. The results demonstrated the feasibility of this model for promoting inclusive and sustainable regional development.DiscussionHowever, certain limitations were identified, such as the heterogeneity of micro-regions, which may hinder comparisons across municipalities. These constraints highlight the need for further research to refine and expand this type of analysis. Thus, the present study represents a starting point for the design of regional development strategies that respect cultural diversity and foster sustainability.